Transformation of Emergency Department Services through Hospital Management Information System: A Case Study of Bakti Pajajaran Regional General Hospital - Dani Nurachman; Vishnu Juwono (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
This study examines the digital transformation of Emergency Department services through the Hospital Management Information System at Bakti Pajajaran Regional General Hospital, Bogor Regency. Digital transformation has become a strategic necessity for improving public service quality, bureaucratic efficiency, and patient safety. The study aims to analyze the dynamics of digital transformation in emergency services from a public administration perspective and identify its contribution to service efficiency and patient safety. Using a qualitative post-positivist approach, data were collected through in-depth interviews, observation, document analysis, and literature review. The analysis applied a public sector digital transformation framework consisting of transformation reasons, objects, processes, and results. The findings show that digital transformation was driven by the need to improve service quality, advances in information technology, and national regulatory demands. The system improved service efficiency by accelerating access to patient data, reducing duplicate documentation, and strengthening inter-unit coordination. It also supported patient safety through more complete, accurate, and traceable clinical documentation. However, challenges remain in system interoperability, digital competency, health data governance, and information security.